Makna Simbolik Tradisi Hajat Laut di Pantai Karapyak Pangandaran - Agustina, Deden Dendi; Silviani, Pani; Mulyadi, Febi; Wijayanti, Yeni (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2025)
This research aims to analyse the meaning of the hajat laut tradition in Pangandaran. The research method used is the historical research method which consists of four stages, namely heuristics, verification and criticism, historiography. The results showed that Hajat laut at Karapyak beach Pangandaran is a tradition that is carried out for generations. This tradition is often carried out by the Pangandaran community once a year, namely in the month of Suro or Muharram. Hajat Laut is a preservation of the arts, because it includes music and dance. This ceremony is held to preserve the existing culture of the community and as an expression of gratitude to Allah SWT. In the beginning, the tradition of Hajat Laut was a form of offering from the coastal community of Pangandaran to the ruler of the southern sea that the community believed at that time. However, today the belief is straightened into a form of gratitude to God Almighty.